Vivencias que inciden en el consumo de alcohol en tres adolescentes entre los 15 y 17 años de la Institución Educativa Distrital El Destino, ubicada en la localidad quinta, Bogotá D. C (2021)
This research proposal revolved around the problem of alcohol consumption by students of Colegio El Destino; The objective of this is to understand the experiences that lead to alcohol consumption in three adolescents between 15 and 17 years of the Destino District Educational Institution, in addition to describing some key concepts such as; psychosocial factors, social norms, student environment, and alcohol in general, this also inquired to know the influence of the socio-cultural environment among the three adolescents affected by alcohol consumption in the Destino District Educational Institution, also to explore the incidence of family environment in the consumption of alcohol among the three young people from the El Destino District Educational Institution.